A people and a key to philosophize (PerCursos, 2021)
Unprecedent times to reflect and ponder: Is it possible to claim an unified way of thinking? Will these circumstances help us catch a glimpse of another way to be in the world? To tear modern and post-modern parameters we need to view things from a different perspective. Dussel describes this as a new way of creating the world, transmodernity. The means to recognize and live other worlds are diverse and unknown, we will show one that existed centuries ago, when we weren't America yet and colonization, an imposition that tried to silence native peoples, didn't exist. By aiming at a decolonizing atitute, we invite ourselves to experiment an "insertion or interculturation" or an "indigenization"; they are possibilities to surpass the dominant racional paradigm and acess the ‘ayxa sk’ujol, to be between humans "with heart" and "not between cerebrals". A possible way to acess this ancestral knowledge requires a contextual key upon an unknown and disregarded language. We'll use Lenkersdorf in his book “Filosofar en clave tojolabal” as well as some papers written by mayan people on the contemporary resistance's struggle. The Mayan language has the sound "tic" as sufix and it's the key that makes we, westerns, baffled, confused or is beyond our understanding.
Keywords: Indigenization; Indigenous philosophy; Decolonial philosophy